Putra Daerah Membangun Daerah Melalui Literasi Kinerja Keuangan Pemerintah Daerah - Fitra Ria Silvida; Aulia Zanuarisma; Meila Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
The results of the pre-test and post-test in this service show that local students, in this case MA students, are old enough to be considered capable of logical thinking and are considered to have advantages in understanding the social, cultural context and local potential of Mojokerto Regency. So that it can become an agent of change in encouraging more transparent, efficient and accountable financial governance. Good financial literacy contributes to increasing Regional Original Income (PAD), spending efficiency, and budget management that is oriented to community needs. To achieve this, this service invites and encourages MA Al Kautsar students to think critically, logically and encourages students to have concern for Mojokerto Regency. Students are encouraged to choose roles that can contribute to the better development of Mojokerto Regency. The post test results show that students plan to choose roles that are oriented towards developing personal skills which also have an impact on solving community problems, for example becoming health workers, education workers, and even improving skills in understanding religion such as memorizing the Koran. This service article recommends increasing the capacity of local youth through continuous training, strengthening collaboration between government and society, and applying modern technology to increase financial transparency. With this approach, Mojokerto Regency can realize better financial governance and inclusive and sustainable development through human resources who are active, intelligent and care about the progress of the region.